A dinâmica de centralização e descentralização politica e administrativa e a revisão da malha territorial municipal da região norte do Brasil (1988 – 2010) - Gilberto de Miranda Rocha (Confins)
This article aims to analyze the changes in the municipal grid in the Northern Region of Brazil from 1988 to 2010. The review of the political loop - administrative city in Brazil, would be related directly to multiple factors, among which include: changes in Brazilian political and institutional order, especially with regard to alternating periods of centralization and decentralization of political administration, the redistribution of population in the territory and the urbanization process. These factors were significant in Northern Brazil. In the period from 1988 to 2010, this region experienced in percentage terms, the highest rate of growth in the number of municipalities in the country, 119%. Also witnessed profound demographic change: changes in population distribution with the internalization of the population and urbanization. Fees relating to the pace of urban population growth in the region were above the national average